Trunk muscle activation, fatigue and low back pain in tennis players. Issue 4 (April 2016) - Correia, José Pedro; Oliveira, Raul; Vaz, João Rocha; Silva, Luís; Pezarat-Correia, Pedro
Abstract: Objectives: To analyze differences in trunk endurance time, fatigue and activation in tennis players with and without low back pain. Design: Observational study, cross-sectional design. Methods: Thirty-five tennis players completed an isometric trunk endurance protocol comprising four tasks (flexor, extensor and side bridge tests). LBP history was obtained through the Nordic Musculoskeletal Questionnaire. Endurance time was recorded for each test. Surface electromyographic activity was recorded bilaterally from rectus abdominis, external obliques, iliocostalis lumborum and longissimus thoracis. Average electromyographic amplitude and median frequency slopes during the tests were calculated and used as indicators of change in muscle activation and fatigue. Results: Asymptomatic players had greater flexor ( p  = 0.004) and right side bridge ( p  = 0.043) endurance times. These players produced a greater increase in avrEMG during the right side bridge test for the left ES-I ( p  = 0.046) and right EO ( p  = 0.008). Players with LBP in the last 7 days showed reduced activation of the left ( p  = 0.014) and right ( p  = 0.013) ES-I and left longissimus thoracis (ES-L, p  = 0.047) in the extensor test. In the left side bridge test there was a lower avrEMG slope of the left EO ( p  = 0.024) and left RA MF slope ( p  = 0.011). In the right side bridge test a lower left ES-I avrEMG slope was found ( p  = 0.048). Conclusions: Symptomatic players show lower activation of extensor muscles, less co-contraction patterns and less abdominal endurance. Tennis coaches and clinicians should consider these factors in their approach to players with LBP.